On the relationship between EU regional policy and national regional development aid: im Rahmen der Bund-Länder-Gemeinschaftsaufgabe „Verbesserung der regionalen Wirtschaftsstruktur” (GA) - Tetsch, Friedemann (Raumforschung und Raumordnung | Spatial Research and Planning, 2002)
For many years, the EU Commission has pursued a policy of marginalising the role of the Member States in the field of regional policy. This article sets out the implications of the centralistic approach adopted by the EU Commission for regional development policy within Germany, highlighting the conflicts which ensue in the relationship between the Federal and Land (state) governments, on the one hand, and between the Federal government and the Commission. In view of the impending enlargment of the EU to the east, the author identifies an urgent need for a fundamental overhaul of EU structural policy, and equally for a new approach at EU level to controlling the provision of regional aid within Member States.
Keywords: Article